Técnica não destrutiva para análise da interação de linhas de campo magnético e material - Leite, João Pereira (2014)
The use of ferromagnetic materials such as steel have been abundant in products and manufacturing equipment due to their magnetic properties, which generates an interaction between them and the applied magnetic fields. This interaction has been studied for the development of Non-Destructive Testing (NDT) used to detect cracks, heterogeneity, degree of deformation and accompanying precipitation of desirable and / or undesirable phases in materials. In this work a NDT technique based on the application of magnetic fields in the region of reversal of the magnetic materials has been developed. There were compared an SAE 1045 steel and an ASTM 6261 aluminum alloy, being then classified as paramagnetic and ferromagnetic, respectively. It was tried to knowledge of how the variables metallographic geometry and texture could interfere with magnetic induction (B) in these materials. It was determined the values of H and optimum thickness, the equations relating the geometry, thickness, and shape of the samples had magnetic anisotropy and rotating the samples. The technique proved promising with both materials interacted with the magnetic field applied by working in a common region for the two materials magnetization, the magnetic region of reversibility. The method was sensitive to metallographic texture, being promising for determining the best direction of magnetization in materials for electrical purposes. The geometry of the samples influenced the amount of magnetic induction, carrying out mathematical corrections for the comparison of different shapes, sizes, thicknesses and materials is required. For the SAE 1045 steel was magnetic anisotropy due to the existence of metallographic texture from the manufacturing process by rolling steel. For aluminum ASTM 6261 did not occur in magnetic anisotropy due to the lack of metallographic texture.